Working on Molière's Bourgeois gentilhomme working sessions - Lully, Jean-Baptiste 1632-1687 (Tourbillon, 2006)
On November 10, 2004, Molière's Bourgeois Gentilhomme was produced in Paris, at the Trianon. In this documentary, you can follow the actors' work on diction and their effort to recreate the language and declamation style of the 17th century. The Bourgeois Gentilhomme was originally a command by King Louis XIV to Molière and Lully. The playwright and the composer were asked to compose a true and intelligent "comédie-ballet". In 1670, they presented a timeless masterpiece. Molière was an expert both in human psychology and in creating hilarious situations in which the characters are all caught. In this play, he playfully mixes several genres: the buffoonery, the salacious and the satire. The troop presented in the documentary is very coherent and embodies perfectly the type characters in the Bourgeois Gentilhomme. Lully's music comes to refine the portraits drawn by the writer and reinforces the comical side of this fantastic comedy